Persistent and emerging pollutants in the blood of German adults: Occurrence of dechloranes, polychlorinated naphthalenes, and siloxanes. (December 2015) - Fromme, Hermann; Cequier, Enrique; Kim, Jun-Tae; Hanssen, Linda; Hilger, Bettina; Thomsen, Cathrine; Chang, Yoon-Seok; Völkel, Wolfgang
Abstract: Human biomonitoring is a valid method to determine exposure, identify time trends, and monitor the effects of restrictions and measures. To characterize the recent exposure of Germans to persistent or emerging substances, we analyzed 4 dechloranes, 33 polychlorinated naphthalenes (PCNs), and 3 cyclic volatile methyl siloxanes (cVMS) in 42 plasma samples. The samples were collected from blood donors on a random selection. The median values of both Dechlorane Plus (DDC-CO) isomers were 1.23 ng/g l.w. for anti - and 0.77 ng/g l.w. for syn –DDC-CO. The two other dechloranes were found at lower levels. The median level of ∑ − PCNs was 575 pg/g l.w. (range: 101–1406 pg/g l.w.). On average, the levels of PCNs in plasma were dominated by the congeners CN73, CN66/67, and CN51, which were responsible for approximately 71% of the total amount of PCNs. The cVMS octa-, deca-, and dodecamethylcyclotetrasiloxane could be determined in only some samples, with maximum values of 0.73, 0.48, and 0.79 μg/l, respectively. Regarding dechloranes, our results are similar to those from other western countries but slightly lower than results from China. The levels of PCNs in German blood are similar to those observed in the U.S.A., but considerably lower than those reported for Korea. Using a preliminary TEF (toxic equivalency factor), the mean TEQ of the 9 quantifiable PCNs in Germany was low (0.36 pg TEQ/g l.w.). The PCN levels in our study group are lower compared to previous studies. Highlights: We have analyzed persistent and emerging substances in blood samples. Targets are dechloranes, polychlorinated naphthalenes, and cyclic methyl siloxanes. Levels of dechloranes are similar to other western countries but lower than in China. Concentrations of PCNs and cVMS are low in Germany.